2021
DOI: 10.1111/hir.12395
|View full text |Cite
|
Sign up to set email alerts
|

New nurses apply only basic source evaluation criteria but realize their skills are lacking: More sophisticated approaches to teaching evaluation skills are required

Abstract: Background: While information evaluation is an essential component of evidence based practice, it remains unclear how nurses perceive their own source evaluation skills and what evaluation criteria they typically apply.Objectives: This study aims to determine nurses' self-reported confidence in their evaluation skills and their actual source evaluation ability. The findings will guide information literacy instruction. Methods:A questionnaire asked recently graduated nurses from four institutions in the Intermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The authors conclude by advocating for academic libraries to develop roles for data librarians to help train researchers in the processes required for safe data preparation for sharing. A questionnaire survey was also used by Schvaneveldt et al (2022) of the self‐assessed levels of confidence of recently graduated nurses in evaluating information. While nurses' confidence levels about source evaluation largely matched their ability, findings indicated that they apply only basic source evaluation criteria that did not match the recommended criteria by professional organisations.…”
Section: In This Issue…mentioning
confidence: 99%
“…The authors conclude by advocating for academic libraries to develop roles for data librarians to help train researchers in the processes required for safe data preparation for sharing. A questionnaire survey was also used by Schvaneveldt et al (2022) of the self‐assessed levels of confidence of recently graduated nurses in evaluating information. While nurses' confidence levels about source evaluation largely matched their ability, findings indicated that they apply only basic source evaluation criteria that did not match the recommended criteria by professional organisations.…”
Section: In This Issue…mentioning
confidence: 99%